Interleaved deep brain stimulation for dyskinesia management in Parkinson's disease. Issue 11 (4th September 2019) - Aquino, Camila C.; Duffley, Gordon; Hedges, David M.; Vorwerk, Johannes; House, Paul A.; Ferraz, Henrique B.; Rolston, John D.; Butson, Christopher R.; Schrock, Lauren E.
Abstract: Background: In patients with Parkinson's disease, stimulation above the subthalamic nucleus (STN) may engage the pallidofugal fibers and directly suppress dyskinesia. Objectives: The objective of this study was to evaluate the effect of interleaving stimulation through a dorsal deep brain stimulation contact above the STN in a cohort of PD patients and to define the volume of tissue activated with antidyskinesia effects. Methods: We analyzed the Core Assessment Program for Surgical Interventional Therapies dyskinesia scale, Unified Parkinson's Disease Rating Scale parts III and IV, and other endpoints in 20 patients with interleaving stimulation for management of dyskinesia. Individual models of volume of tissue activated and heat maps were used to identify stimulation sites with antidyskinesia effects. Results: The Core Assessment Program for Surgical Interventional Therapies dyskinesia score in the on medication phase improved 70.9 ± 20.6% from baseline with noninterleaved settings ( P < 0.003). With interleaved settings, dyskinesia improved 82.0 ± 27.3% from baseline ( P < 0.001) and 61.6 ± 39.3% from the noninterleaved phase ( P = 0.006). The heat map showed a concentration of volume of tissue activated dorsally to the STN during the interleaved setting with an antidyskinesia effect. Conclusion: Interleaved deep brain stimulation using the dorsal contacts can directly suppress dyskinesia, probably because of the involvement of the pallidofugal tract, allowing more conservative medication reduction. © 2019 International Parkinson and Movement Disorder Society